1990
DOI: 10.1111/j.1365-2249.1990.tb05235.x
|View full text |Cite
|
Sign up to set email alerts
|

T cell reactivity to the purified mycobacterial antigens p65 and p70 in leprosy patients and their household contacts

Abstract: SUMMARYT cell reactivity to the 70 and 65 kD (p70 and p65) protein antigens derived from Mycobacterium bovis BCG strain was studied by measuring the proliferative responses of peripheral blood mononuclear cells from members ofan isolated Aboriginal eommunity resident in the Torres Straits islands. In tbe nine index leprosy cases the pattern of responsiveness to the purified antigens paralleled that to whole sonicates from M. leprae and BCG. In the 40 contacts of tbe index cases, a high correlation was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 9 publications
1
2
1
Order By: Relevance
“…leprae hsp65. Many authors have observed, as in our study, that while cells from healthy contacts and PB patients proliferated against mycobacterial hsp65, most LL patients failed to respond to this protein fraction [11,[39][40][41]. These results are opposed to those of Mendez-Samperio et al [42], who observed higher responses in LL than in TT patients.…”
Section: Discussioncontrasting
confidence: 57%
“…leprae hsp65. Many authors have observed, as in our study, that while cells from healthy contacts and PB patients proliferated against mycobacterial hsp65, most LL patients failed to respond to this protein fraction [11,[39][40][41]. These results are opposed to those of Mendez-Samperio et al [42], who observed higher responses in LL than in TT patients.…”
Section: Discussioncontrasting
confidence: 57%
“…In vitro lymphoproliferative responses to rML65 were observed in a considerable proportion of tuberculoid leprosy patients, healthy contacts and non-contacts. A similar finding has been reported for the 65-kD antigen of BCG [17,18]. Compared with these reports, the proportion of responders to rML65 is low in our study, and this may quite well be due to the stringent criteria we have used for defining the positive response.…”
Section: Discussionsupporting
confidence: 90%
“…The mycobacterial 65-kD antigen has also been demonstrated to be a major T cell immunogen in mice [9,10]. Several studies have demonstrated the presence of T cells reactive to the mycobacterial 65-kD antigen in humans by deriving specific helper and cytotoxic T cell clones from leprosy and tuberculosis patients and healthy volunteers [11][12][13][14][15], However, population studies in leprosy patients and healthy endemic controls are required to evaluate the true immunological significance ofthe recombinant antigens [16], There are only a very few such studies on cellular and humoral immune responses to the mycobacterial 65-kD antigen [17][18][19][20][21], Further, both responses were not evaluated together in any of these investigations. Therefore, we studied the lymphoproliferative response and IgG and IgM antibody levels to the recombinant Myco.…”
Section: Introductionmentioning
confidence: 99%
“…The localized accumulation of hsp70 could contribute to the immunopathology of leprosy reactions. Hsp70 from lysed cells may be presented via HLA class II molecules to an immune sy.stem already primed for recognition of the bacterial homologue [28], and may amplify or prolong the inflammatory response, while cytoplasmic hsp presented by HLA class I molecules could provide targets for potentially damaging cytolytic T cells. Hsp autoreaetive cytolytic T cells have been shown to recognize macrophages stressed in in vitro cell culture experiments, although this was mediated via hsp60 rather than hsp70 [29].…”
Section: Discussionmentioning
confidence: 99%